2014
DOI: 10.4168/aair.2014.6.5.470
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Rhinoconjunctivitis due to Maize in a Snack Processor: A Cross-Reactivity Study Between Lipid Transfer Proteins From Different Cereals and Peach

Abstract: We report the case of a snack processor who developed occupational rhinoconjunctivitis due to maize brand exposure during the extrusion process, and who experienced abdominal pain upon drinking beer. The allergens implicated and the cross-reactivity between non-specific lipid transfer proteins (LTPs) from different cereals and peach were investigated. Skin prick tests and specific IgE to cereal flours, pulmonary functions tests and specific conjunctival and inhalation challenges to maize extract were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…19,64 nsLTP in a variety of foods has also been shown to be relevant in occupational allergy in those involved in processing other plant food crops including asparagus, wheat and maize. 9,[65][66][67][68][69] Rodriguez and colleagues generated animal models of anaphylaxis to Pru p 3 following sensitization via the nasal route in combination with lipopolysaccharide (LPS). 70 Recently, Rosace et al have described a progressive remodelling process of the oral mucosa, along with respiratory allergy progression, using profilin as an allergen.…”
Section: Routes Of Sensitization To Nsltpmentioning
confidence: 99%
“…19,64 nsLTP in a variety of foods has also been shown to be relevant in occupational allergy in those involved in processing other plant food crops including asparagus, wheat and maize. 9,[65][66][67][68][69] Rodriguez and colleagues generated animal models of anaphylaxis to Pru p 3 following sensitization via the nasal route in combination with lipopolysaccharide (LPS). 70 Recently, Rosace et al have described a progressive remodelling process of the oral mucosa, along with respiratory allergy progression, using profilin as an allergen.…”
Section: Routes Of Sensitization To Nsltpmentioning
confidence: 99%
“…Work-related respiratory symptoms (WRS), including upper and lower respiratory symptoms, are frequently found in bakery workers, with an incidence of 3%-17% for lower respiratory symptoms and an 11%-30% for upper respiratory ones 1. The sensitization rate for wheat flour ranges from 2% to 15%,1 and risk factors for the sensitization and development of baker's asthma are atopy, exposure intensity, and genetic susceptibility 7891011…”
Section: Introductionmentioning
confidence: 99%
“… 6 8 Food processors may affect IgE-mediated allergic occupational diseases through halation of airborne particles, skin contact, or ingestion. Daiana et al 10 reported occupational rhinoconjunctivitis due to maize in a snack processor. Here, we present a case of occupational, IgE-mediated papain allergy who works in a sausage processing factory.…”
Section: Introductionmentioning
confidence: 99%